Nevves from Virginia : the lost flocke triumphant : with the happy arriuall of that famous and worthy knight Sr. Thomas Gates : and the well reputed & valiant captaine Mr. Christopher Newporte, and others, into England : with the maner of their distresse in the Iland of Deuils (otherwise called Bermoothawes) where they remayned 42. weekes, & builded two pynaces, in which they returned into Virginia - Rich, Richard, active 1610 (LLMC-digital (Series), 1610)
A poem entitled "Newes from Virginia: the lost flocke triumphant," written by Robert Rich and printed in London in 1610. Included in this text is an introduction to the readers, as well as the verses which described the adventures of the Sea-venture ship, the storm and shipwreck that sent them to Bermuda instead of Virginia, and its ultimate arrival in Virginia and return to England.